DETERMINATION OF OPTIMUM AB-MIX CONCENTRATION FOR BRASSICA SPP. ON NFT HYDROPONIC SYSTEM - Tarigan, Puji Lestari; Halimah, Nur (Fakultas Pertanian Universitas Tanjungpura, 2026)
Hydroponics serves as an alternative to conventional land-based agriculture. This technique enables the cultivation of vegetables in regions with poor fertility or limited space and high population density. The hydroponic planting system's advantage is based on its ability to precisely regulate nutrients. Ensuring adequate nutrition will yield optimal outcomes and be economically efficient. A hydroponic system has long been used to grow pakchoy and samhong plants. The purpose of this study is to ascertain how best to utilize AB-Mix nutrition to achieve the best growth possible for both varieties of mustard. The experiment uses a Completely Randomized Design (CRD) factorial. The first factor are concentrations of AB-mix, 1000 ppm, 1200 ppm, and 1400 ppm. The second factor is Brassica spesies are samhong and pakcoy. There are six treatment combinations, and they were repeated five times. Observations on plant height and leaf number are carried out for four weeks. ANOVA was used to test the observation data, and DMRT was used for additional testing. The pakcoy and samhong plants' plant height were best achieved when an AB-Mix concentration of 1200 ppm was used.